The Impact of Family Support and Patient Dependency on Quality of Life in Stroke Patients Receiving Home Care: A Study at Hospital - Menik Kustriyani; Fahri Husny; Arief Yanto; Aprin Rusmawati (Journal Of Nursing Practice, 2025)
Background: Stroke is a leading cause of disability worldwide, significantly affecting patients' quality of life. Family support and patient dependency are critical factors influencing recovery and well-being during home care. Purpose: This study aimed to examine the relationship between family support, patient dependency, and quality of life among stroke patients attending outpatient clinics at RSUD Gondo Suwarno Ungaran. Methods: A correlational study was conducted from February to March 2025 involving 48 stroke patients. Data on family support, patient dependency (Barthel Index), and quality of life were collected through validated instruments and analyzed using Pearson correlation. Results: The mean family support score was 40.67 (±3.95), patient dependency score was 61.35 (±23.65), and quality of life score was 61.23 (±96.59). Significant positive correlations were found between family support and quality of life (r = 0.376, p = 0.008) and between patient dependency and quality of life (r = 0.853, p = 0.0001). Conclusion: Both family support and patient dependency levels are significantly associated with quality of life in stroke patients during home care. Enhancing family involvement and managing patient dependency may improve patient outcomes.